Drosophila Lis1 is required for neuroblast proliferation, dendritic elaboration and axonal transport. - Liu, Z.; Steward, R.; Luo, L. (Nature Cell Biology, 2000)
Haplo-insufficiency of human Lis1 causes lissencephaly. Reduced Lis1 activity in both humans and mice results in a neuronal migration defect. Here we show that Drosophila Lis1 is highly expressed in the nervous system. Lis1 is essential for neuroblast proliferation and axonal transport, as shown by a mosaic analysis using a Lis1 null mutation. Moreover, it is cell-autonomously required for dendritic growth, branching and maturation. Analogous mosaic analysis shows that neurons containing a mutated cytoplasmic-dynein heavy chain (Dhc64C) exhibit phenotypes similar to Lis1 mutants. These results implicate Lis1 as a regulator of the microtubule cytoskeleton and show that it is important for diverse physiological functions in the nervous system.